ASSESSMENT OF BONE TISSUE CONDITION BY METHOD OF COMPUTED TOMOGRAPHY IN PTS WITH RHEUMATOID ARTHRITIS - T A Raskina; V A Ushakov (Научно-практическая ревматология)
Aim: To estimate the bone mineral density (BMD) in patients with dilVerent variants of rheumatoid arthritis (RA). Materials and methods: The study included 65 patients with the acknowledged RA, who were not treated with corticosteroids, basic remedies and antiosteoporosis therapies. The group comprises 26 women оГ reproductive age (I group) and 28 women in postmenopause period. The investigations were held with the computer tomograph “Tomoscan” Philips. Results: The comparative analysis of BMD disorders frequency in the studied groups shows that in RA women of postmenopause period osteopenia accounts for 57,1%, osteoporosis - for 32,1% of patients, which is twice as often as in premenopausal women period: 30,8% and 15,4% respectively. BMD levels in RA are correlated with rheumatoid lactor, destructive tendency in bones and high activity of disease.